Discerning ideal blackgram (Vigna mungo) genotypes using multi-trait genotype ideotype distance index - BABU, D RATNA; BARATHI, M BALA; AYESHA, Md; PRASANNA, K LAKSHMI; ANURADHA, N (The Indian Journal of Agricultural Sciences, 2024)
Meticulous identification of ideal parental types with most of the improved traits is essential to develop superior varieties. The recently developed genotype-ideotype distance based selection index furnished an improved way in selection of ideal genotypes in plant breeding. The present experiment was conducted during rainy (kharif) seasons of 2021 and 2022 at research farm of Agricultural College (Acharya N. G. Ranga Agricultural University), Bapatla, Andhra Pradesh to identify potential blackgram [Vigna mungo (L.) Hepper] genotypes with majority of the improved traits. A total of 127 blackgram genotypes were analyzed by using Multi-trait Genotype Ideotype Distance Index (MGIDI) to select superior genotypes with improved traits. MGIDI provided selection differential and selection gain for all the traits with desired values. After varimax rotation, 10 traits were grouped under 4 factors, which cumulatively explained about 76.4% of total variance with eigen value more than 1. Out of 127 studied blackgram genotypes, MGID index identified 6 superior genotypes (GAVT 12, GAVT 7, TBG 106, VBG 13-003, GBG 12 and MBG 1046) at 5% selection intensity. Per cent contribution of factors towards the MGIDI values indicated that, the factor 3 which includes days to maturity, plant height and pod length contributed least and factor 1 which includes grain yield/plant, clusters/plant, pods/plant and seeds/pod contributed most. These selected genotypes with superior per se performance for multiple traits based on the MGIDI can be used as genitors in any hybridization programme to develop superior varieties in turn improving the blackgram productivity.